Knowledge Level of Families For Anticipate Covid 19 in Sukabumi - Danismaya, Irawan; Safariyah, Erna (KnE Life Sciences, 2021)
Many members of the public have admitted that they are confused by the threat of Covid-19. Contagion risk between family members is high. The family must be able to decide what to do if any of its members are infected. The goal of this study was to identify the knowledge held by families in a specific region relating to the virus’ nature, the source of contagion, the infection mechanisms, and infection prevention methods. Data collection was conducted on 1,719 families aged from 20 – 95 years using the cross-sectional method. Respondents were chosen from the green zone area using Purposive Sampling. They were asked to fill the questionnaire using a Google form. The information sources used by the respondents were television, internet, and social media groups. The results show eight criteria of knowledge relating to Covid-19. Keywords: anticipate Covid-19, knowledge, family